Combined Respiratory Chain Deficiency and UQCC2 Mutations in Neonatal Encephalomyopathy: Defective Supercomplex Assembly in Complex III Deficiencies. (19th July 2017) - Feichtinger, René G.; Brunner-Krainz, Michaela; Alhaddad, Bader; Wortmann, Saskia B.; Kovacs-Nagy, Reka; Stojakovic, Tatjana; Erwa, Wolfgang; Resch, Bernhard; Windischhofer, Werner; Verheyen, Sarah; Uhrig, Sabine; Windpassinger, Christian; et al.
Abstract : Vertebrate respiratory chain complex III consists of eleven subunits. Mutations in five subunits either mitochondrial (MT-CYB) or nuclear (CYC1, UQCRC2, UQCRB, and UQCRQ) encoded have been reported. Defects in five further factors for assembly (TTC19, UQCC2, and UQCC3) or iron-sulphur cluster loading (BCS1L and LYRM7) cause complex III deficiency. Here, we report a second patient with UQCC2 deficiency. This girl was born prematurely; pregnancy was complicated by intrauterine growth retardation and oligohydramnios. She presented with respiratory distress syndrome, developed epileptic seizures progressing to status epilepticus, and died at day 33. She had profound lactic acidosis and elevated urinary pyruvate. Exome sequencing revealed two homozygous missense variants in UQCC2, leading to a severe reduction of UQCC2 protein. Deficiency of complexes I and III was found enzymatically and on the protein level. A review of the literature on genetically distinct complex III defects revealed that, except TTC19 deficiency, the biochemical pattern was very often a combined respiratory chain deficiency. Besides complex III, typically, complex I was decreased, in some cases complex IV. In accordance with previous observations, the presence of assembled complex III is required for the stability or assembly of complexes I and IV, which might be related to respirasome/supercomplex formation.